Intestinal IgA production and its role in host-microbe interaction - Gutzeit, Cindy (2014)
Complex and diverse communities of bacteria establish mutualistic and symbiotic relationships with the gut after birth. The intestinal immune system responds to bacterial colonization by acquiring a state of hypo-responsiveness against commensals and active readiness against pathogens. The resulting homeostatic balance involves a continuous dialog between the microbiota and lymphocytes with the intermediation of epithelial and dendritic cells. This dialog causes massive production of immunoglobulin A (IgA), a non-inflammatory antibody specialized in mucosal protection. Here, we discuss recent advances on the regulation of intestinal IgA responses and their role in host-microbe interaction.